Electroactive γ-phase, enhanced thermal and mechanical behaviour and high ionic conductivity response of poly (vinylidene fluoride)/cellulose nanocrystals hybrid nanocomposites - Lizundia, E. (2020)
Cellulose nanocrystals (CNCs) were incorporated into poly (vinylidene fluoride) (PVDF) to tailor the mechanical and dielectric properties of this electroactive polymer. PVDF/CNC nanocomposites with concentrations up to 15 wt.% were prepared by solvent-casting followed by quick vacuum drying in order to ensure the formation of the electroactive γ-phase. The changes induced by the presence of CNCs on the morphology of PVDF and its crystalline structure, thermal properties, mechanical performance and dielectric behavior are explored. The results suggest a relevant role of the CNC surface −OH groups, which interact with PVDF fluorine atoms. The real dielectric constant ε’ of nanocomposites at 200 Hz was found to increase by 3.6 times up to 47 for the 15 wt.% CNC nanocomposite due to an enhanced ionic conductivity provided by CNCs. The approach reported here in order to boost the formation of the γ-phase of PVDF upon the incorporation of CNCs serves to further develop cellulose-based multifunctional materials